2010
DOI: 10.1039/c002199g
|View full text |Cite
|
Sign up to set email alerts
|

High quality self-assembly magnetite (Fe3O4) chain-like core-shell nanowires with luminescence synthesized by a facile one-pot hydrothermal process

Abstract: Large scale synthesis of uniform self-assembly Fe(3)O(4)@phenol formaldehyde resin (PFR) core-shell nanowires with 80-100 nm in diameter and 20-30 microm in length can be realized by a one-pot hydrothermal process. The optical and magnetic properties of the as-synthesized Fe(3)O(4) nanostructures have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…The high resolution TEM image shown in Fig. 2B illustrates the well-ordered lattice fringes with 0.485 nm spacing, which corresponded to the (1 1 1) plane of Fe 3 O 4 [33]. The remaining carbon coating layer and background were derived from PVP, which was not fully decomposed.…”
Section: Synthesis and Characterization Of Tri-functional Microparticlesmentioning
confidence: 99%
“…The high resolution TEM image shown in Fig. 2B illustrates the well-ordered lattice fringes with 0.485 nm spacing, which corresponded to the (1 1 1) plane of Fe 3 O 4 [33]. The remaining carbon coating layer and background were derived from PVP, which was not fully decomposed.…”
Section: Synthesis and Characterization Of Tri-functional Microparticlesmentioning
confidence: 99%
“…Pertinent targets include the synthesis of materials that have desirable anisotropic properties for electronic and optical devices. [6][7][8][9] As this is a difficult task, different techniques have been employed including magnetic-field-induced (MFI) assembly, [10][11][12][13][14][15][16] electric or magnetic dipole-dipole interactions, [17][18][19][20] crystallographically specific orientation, [21] non-uniform stabilizer distribution, [22] templated synthesis [23,24] to produce 1D nanostructured materials. However, an elegant approach would be to construct 1D chains consisting of structurally intricate units and functions.…”
mentioning
confidence: 99%
“…The alignment of the PLL aggregates containing MNP and HPTS along the direction of the applied magnetic field with simultaneous cross-linking by GA results in 1D aligned MFS structures ( Figure 2). The aligned MFS are prepared at various R values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as shown in the Supporting Information ( Figure S6 and Table S1) with R = 10 as the optimum condition used for evaluation of their properties.…”
mentioning
confidence: 99%
“…All of detected diffraction peaks can be indexed as spinel magnetite, which is in good agreement with standard literature data (JCPDF card number: 86-1354), (Gong et al 2010). These sharp diffraction peaks clearly revealed that spinel magnetite product is well defined crystallites, with no impurity diffraction peaks, indicating a pure phase of synthesized magnetite nanoparticles.…”
Section: Preparation and Characterization Of Fe3o4@nh2-sio2 Nanopartimentioning
confidence: 77%